IMPLEMENTASI PEMBELAJARAN QIRA’AT AL-SAB’ “STUDI OBSERVASI BERDASARKAN TEORI AZ-ZARKASYI DI PONDOK PESANTREN HIDAYATUL MUBTADI’AT AL-QUR’ANIYAH LIRBOYO KEDIRI” - Dewi Bahrotul Ilmiah (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
The Hidayatul Mubtadi’at Al-Qur'aniyah Lirboyo Kediri Islamic Boarding School is an Islamic boarding school that to this day continues to maintain the tradition of teaching qira'at sab'ah. This research aims to describe the methods and systematics of teaching qira'at sab'ah in Islamic boarding schools using a qualitative approach and using phenomenological methods. Data analysis was carried out using Al-Zarkasyi's theory. The Hidayatul Mubtadi’at Al-Qur'aniyah Lirboyo Islamic Boarding School applies qira'at sab'ah learning using the talaqqi and musyafahah methods. The talaqqi method is carried out intensively in the presence of the teacher, ensuring that not a single verse escapes the teacher's attention. Meanwhile, in the musyafahah process, students are guided by senior ustadzah or those who have completed qira’at al-sab‘ in the previous year, including guidance on how to pronounce various types of qira’at, such as imalah, taqlil, hadzf hamzah, ikhtilash, tashil, and so on . If there are differences in the qira'at, students can immediately ask their teacher. The systematics include two stages: first, jama‘ sughro (combining two narrators from each qari’); second, jama‘ kubro (a combination of qira'at from all the seven imams of the qurra’).